THE RELATIONSHIP BETWEEN COMMON MENTAL DISORDERS AND EMOTIONAL EATING AND NUTRITIONAL STATUS OF STUDENTS IN HASANUDDIN UNIVERSITY STUDENT DORMITORY, 2023: THE RELATIONSHIP BETWEEN COMMON MENTAL DISORDERS AND EMOTIONAL EATING AND NUTRITIONAL STATUS OF STUDENTS IN HASANUDDIN UNIVERSITY STUDENT DORMITORY, 2023 - Mulya Salsabila, Nada; Hidayanty, Healthy; Indriasari, Rahayu; Amalia, Marini; Fajarwati Ibnu, Indra (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2024)
ABSTRAK Pendahuluan: Status gizi memainkan peran penting dalam perkembangan manusia, terutama bagi mahasiswa untuk perkembangan intelektualnya. Salah satu faktor yang dapat secara tidak langsung memengaruhi status gizi yaitu faktor psikologis dan mekanisme penanganan stres, seperti gangguan mental umum dan perilaku makan emosional. Ketika kondisi-kondisi ini berlangsung dalam jangka panjang, mereka dapat berdampak negatif pada status gizi seseorang. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara common mental disorders dan emotional eating dengan status gizi pada mahasiswa di Asrama Mahasiswa Universitas Hasanuddin. Bahan dan Metode: Penelitian ini dilakukan pada 245 Mahasiswa di Asrama Mahasiswa Universitas Hasanuddin yang dipilih menggunakan metode proportional random sampling. Status gizi dikur menggunakan indeks massa tubuh (IMT) dengan melakukan pengukuran berat badan dan tinggi badan. Common mental disorders diukur menggunakan Depression, Anxiety, and Stress Scale (DASS). Emotional eating diukur menggunakan Adult Eating Behavior Questionnaire (AEBQ). Analisis menggunakan program SPSS menggunakan uji Chi-Square. Hasil: Rata-rata usia responden (20 tahun ± 1,6), mayoritas perempuan, tertinggi pada rumpun fakultas sosial-humaniora (46,5%), mayoritas angkatan 2021 (29%), sebanyak 57,6% bukan penerima beasiswa, tertinggi pada lama tinggal 1-12 bulan (51%), dan mayoritas UKT golongan 0-2 (52,7%). Sebanyak 33,9% mengalami status gizi kurang (kurus dan sangat kurus), dan sebanyak 13,4% mengalami status gizi lebih (gemuk dan obesitas). Sebanyak 37,1% mengalami common mental disorders, termasuk depresi ringan (6,9%), sedang (6,5%), berat (1,6%), kecemasan ringan (15,1%), sedang (12,2%), berat (2,9%), sangat berat (2,0%). Sebanyak 78,8% mengalami emotional eating, dengan 60,8% mengalami emotional under eating dan 28,6% mengalami emotional over eating. Tidak ada hubungan common mental disorders dengan status gizi dengan p-value = 0,300 dan ada hubungan emotional eating dengan status gizi dengan p-value = 0,017. Kesimpulan: Terdapat hubungan antara emotional eating dengan status gizi pada mahasiswa di asrama mahasiswa sehingga perlu adanya upaya lebih lanjut untuk mengganti tindakan mengalihkan stres selain makanan seperti olahraga dan seni. Kata kunci : Common Mental Disorders, Emotional Eating, Status Gizi ABSTRACT Introduction: Nutritional status plays an important role in human development, especially for students for their intellectual development. One of the factors that can indirectly influence nutritional status is psychological factors and stress management mechanisms, such as general mental disorders and emotional eating behavior. When these conditions persist long term, they can negatively impact a person's nutritional status. Objective: This study aims to determine the relationship between common mental disorders and emotional eating and the nutritional status of students at Hasanuddin University Student Dormitory. Methods: This research was conducted on 245 students at Hasanuddin University Student Dormitory who were selected using the proportional random sampling method. Nutritional status is measured using body mass index (BMI) by measuring body weight and height. Common mental disorders are measured using Depression, Anxiety, and Stress Scale (DASS). Emotional eating was measured using the Adult Eating Behavior Questionnaire (AEBQ). Analysis using the SPSS program using the Chi-Square test. Results: Average age of respondents (20 years ± 1.6), majority female, highest in social-humanities faculties (46.5%), majority of class of 2021 (29%), 57.6% not recipients of scholarships, highest the length of stay is 1-12 months (51%), and the majority are in the UKT group 0-2 (52.7%). As many as 33.9% experienced undernutrition status (thin and very thin), and 13.4% experienced overnutrition status (overweight and obese). As many as 37.1% experienced common mental disorders, including mild depression (6.9%), moderate (6.5%), severe (1.6%), mild anxiety (15.1%), moderate (12.2%) %), severe (2.9%), very severe (2.0%). As many as 78.8% experienced emotional eating, with 60.8% experiencing emotional under eating and 28.6% experiencing emotional over eating. There is no relationship between common mental disorders and nutritional status with p-value = 0.300 and there is a relationship between emotional eating and nutritional status with p-value = 0.017. Conclusion: There is a relationship between emotional eating and the nutritional status of students in student dormitories so that further efforts are needed to replace stress diverting actions other than food, such as sport and art. Keywords: Common Mental Disorders, Emotional Eating, Nutritional Status